Hospital Auxiliary Vessel Fore Part Zone Planning to Improve Productivity with Precedence Diagram Method - Wenny Prawati; Intan Baroroh (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The rapid development of Construction Management in Indonesia demands an efficient scheduling system to overcome project complexity. This study focuses on the process of building a hospital ship at one of the large shipyards in East Java, especially in the Fore Part Zone which has a high level of complexity and a limited number of blocks. Delays in this project are caused by several technical constraints such as machine breakdowns and drawing delays. This research aims to improve productivity by using the Precedence Diagram Method (PDM), which enables more optimal work scheduling by overcoming overlapping activities. Three scheduling scenarios were compared: Existing, Plan A, and Plan B. Plan A involved crashing techniques with the addition of overtime hours to accelerate critical Assembly activities (A13 and A14), resulting in a project duration of 301 days and productivity of 74.80 JO/day. Plan B integrated the drawing availability milestone as a prerequisite for the start of fabrication, and applied the same crashing as Plan A. As a result, Plan B was able to complete the project in 284 days with the same productivity, but with a more realistic and adaptive scheduling approach to field conditions. Based on critical path analysis and time efficiency, Plan B is the most optimal schedule for the construction of Fore Part Zone. This research is expected to be a reference in planning and controlling complex ship construction projects.